A utilização do atlas virtual de histologia com o auxílio do caça-palavras como ferramentas de apoio para a educação básica - SOUSA, João Gabriel Teles de (2019)
Educational practices have highlighted the need for (re)construction of the teaching, throught didactic resources that explore the sensorial, psychological and affective aspects of the students related to students' interests and experiences. Some ways to improve and update this process are the use of Didatic Games and Technologies. In this way, this work aims to use the blogspot of virtual atlas content of histology associated with playful play, Caça palavras, in basic education. As methodology, the target audience were students of the 8th grade class of the Elementary and Middle School Tiradentes I. Initially, histological slides were organized for the tissues and organs of animals with elaboration of texts. Then, was built the blog from the Gmail provider and inserted images of biological samples previously identified; in parallel there was the elaboration of a ludic game – caça palavras. As results there was an expositive-theoretical class of histological content, then the Blog was used to demonstrate the images cited in text; then, the class was divided into doubles and conducted a question-answer activity associated with caça palavras; was an interactive and satisfactory moment of the students. From these data, it can be confirmed that digital and / or playful resources serve as an alternative methodology to improve the teaching-learning process in public school students.